Shehu and Formable Integral Transforms on CPCF and CPABC Derivatives - Khalid, Mohd; Akgül, Ali; Attia, Nourhane; Hincal, Evren (Journal of Environmental Accounting and Management, 2026)
In this paper, we address problems that involve the constant proportional Atangana-Baleanu-Caputo (CPABC) and constant proportional Caputo-Fabrizio (CPCF) derivatives. These derivatives introduce new challenges and opportunities in fractional calculus. Our approach is different from traditional methods like the Laplace transform; instead, we use the Shehu and Formable integral transforms to solve these problems. By using these methods, we find solutions that help us understand how systems behave with CPCF and CPABC derivatives.